Home food production buffers against a diet of impoverishment in rural Nepal (PoSHAN). - West, Keith. (Tufts University. Tisch Library., 2016)
Dr. West examines in great detail the diets of women in Nepal, and their likelihood of consuming food based on whether it is purchased or cultivated at their homes.; Nutrition School: NIL Symposium Presentations, 2016.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy